Optimization of Geopolymer Formula Based on Bauxite Tailings Using Curing Temperature and Activator Concentration - Sitanggang, Eva Pramuni Oktaviani; Riysan Octy Shalindry; Shafira Kurnia; Hozaimah; Alyaa Salsabila Nurvi (Rekayasa Sipil, 2026)
The rapid growth of industrialization and urbanization has significantly increased Portland cement consumption, which accounts for approximately 6–7% of global CO? emissions. Geopolymer cement synthesized from industrial waste materials represents a promising low-carbon alternative. This study aims to investigate the feasibility of producing geopolymer cement from red mud, fly ash, and bauxite tailings waste through alkali activation, with emphasis on activator chemistry, concentration, and curing temperature. Geopolymer specimens were prepared using NaOH–Na?SiO? and KOH–K?SiO? activator systems with molarities of 10 M, 12 M, and 14 M, and cured at temperatures of 60 °C, 80 °C, and 100 °C. Mechanical properties, including compressive strength, water absorption, loss in ignition, and specific gravity, were evaluated, supported by XRD and FTIR analyses. The results indicate generally low compressive strength, with a maximum value of 2.10 MPa achieved using 14 M NaOH cured at 60 °C. This limited performance is attributed to incomplete geopolymerization caused by the dominance of crystalline phases that restrict aluminosilicate dissolution. Nevertheless, TCLP results confirm low heavy metal leaching, demonstrating effective immobilization within the geopolymer matrix. These findings highlight the environmental feasibility of red mud–fly ash–based geopolymers while emphasizing the need for compositional and reactivity optimization to enhance mechanical performance.